2017
DOI: 10.1007/s00253-017-8171-2
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of levan production in Bacillus amyloliquefaciens through metabolic optimization of regulatory elements

Abstract: Levan is a functional homopolymer of fructose with considerable applications in food, pharmaceutical and cosmetic industries. To improve the levan production in Bacillus amyloliquefaciens, the regulatory elements of sacB (encoding levansucrase) expression and levansucrase secretion were optimized. Four heterologous promoters were evaluated for sacB expression, and the Pgrac promoter led to the highest level for both sacB transcription and levansucrase enzyme activity. The levan production in the corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…In the 13 Consistent with other reports on microbial levans [21,22], the above analysis suggested that the exopolysaccharide from B. amyloliquefaciens PB6 existed as a levan structure having b-(2,6) linked fructofuranosyl backbone and some b-(1,2!6) linked fructofuranosyl branches with a D-fructosyl or D-glucosyl residue at the end of the main chain. Gu et al [23] reported that, through metabolic optimisation of regulatory elements, the levan production in the recombinant B. amyloliquefaciens strain could be improved to 102 g/L, which was close to the reported highest levan production level in the literature. Considering that B. amyloliquefaciens PB6 is a non-engineered strain and its exopolysaccharide yield was 104 g/L, the confirmation of levan structure in this study implied that levan could be produced from B. amyloliquefaciens PB6 with high safety and a high yield.…”
Section: Identification Of B Amyloliquefaciens Levansupporting
confidence: 70%
“…In the 13 Consistent with other reports on microbial levans [21,22], the above analysis suggested that the exopolysaccharide from B. amyloliquefaciens PB6 existed as a levan structure having b-(2,6) linked fructofuranosyl backbone and some b-(1,2!6) linked fructofuranosyl branches with a D-fructosyl or D-glucosyl residue at the end of the main chain. Gu et al [23] reported that, through metabolic optimisation of regulatory elements, the levan production in the recombinant B. amyloliquefaciens strain could be improved to 102 g/L, which was close to the reported highest levan production level in the literature. Considering that B. amyloliquefaciens PB6 is a non-engineered strain and its exopolysaccharide yield was 104 g/L, the confirmation of levan structure in this study implied that levan could be produced from B. amyloliquefaciens PB6 with high safety and a high yield.…”
Section: Identification Of B Amyloliquefaciens Levansupporting
confidence: 70%
“…A promoter is defined as the region of DNA sequence that initiates the gene transcription (Wrighton, 2018). Promoters are often used together with signal peptides as regulatory elements for the expression and production of recombinant proteins (Guan et al, 2016; Gu et al, 2017; Maffei et al, 2017; Cui et al, 2018). Zhang et al (2016) performed an experimental screen of 138 signal peptides from B. subtilis for the production of an alkali-tolerant xylanase (XynBYG) from Bacillus pumilus BYG.…”
Section: Optimization Of Recombination Protein Secretion By Signal Pementioning
confidence: 99%
“…Levan is a fructose-based homopolysaccharide, a fructan that is mainly composed of β-D-fructofuranose residues linked by β- (2)(3)(4)(5)(6) glycosidic bonds (see Figure 1). It serves both structural and functional roles and stands out from other natural polymers by its unique combination of properties such as strong adhesivity, self-assembly into spherical colloids in water, very low intrinsic viscosity, high biocompatibility, and health benefits, which in turn make this unusual polysaccharide a valuable polymer for various applications in cosmetic, pharmaceutical, food, and other industries [1].…”
Section: Introductionmentioning
confidence: 99%
“…It serves both structural and functional roles and stands out from other natural polymers by its unique combination of properties such as strong adhesivity, self-assembly into spherical colloids in water, very low intrinsic viscosity, high biocompatibility, and health benefits, which in turn make this unusual polysaccharide a valuable polymer for various applications in cosmetic, pharmaceutical, food, and other industries [1]. Whereas levan is also produced by a limited number of plant species at a low degree of polymerization (DP 10-100), longer levan chains (>DP 10 3 -10 4 ) offering a broader spectrum of applications are basically produced by miscellaneous microorganisms both extracellularly and at high titers from sucrose by the hydrolysis and transfructosylation action of levansucrase enzyme [2,3]. Besides mesophilic levan producers from a wide range of genera that include Acetobacter, Bacillus, Erwinia, Gluconobacter, Microbacterium, Pseudomonas, and Zymomonas, as well as many acetic acid and lactic acid bacteria, Halomonas cultures hold distinctive industrial potential due to their added advantages such as high yield and nonsterile production capacity under high salinity [4,5].…”
Section: Introductionmentioning
confidence: 99%